ANDROID APPLICATION FOR AGRICULTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Andriod app is developed to monitor and control whether inside green. greenhouse can be considered as microclimate incubator ,the important parameters inside greenhouse are temperature, soil moisture, humidity, light intensity. These values can be easily measured by using different sensors. They can easily get on android app. we can set threshold values and according to sensors values we can control the devices like water spayer, light bulb, fan or ac. Depending on sensor output controlling action is taken by microcontroller. And by pressing a single button we are control the devices through android app. The objective is to design a simple and easy user friendly system to monitor and control whether inside greenhouse, and control water sprayer, light bulb, cooling fan or ac. The achieved result shows that system is appropriate and working properly.